Model of electronic data interchange (EDI) implementation for Malaysian manufacturing firms - Abdul Hamid, Abu Bakar; Ahmad Anuar, Melati; Krisnapillai, Gengeswari (Faculty of Management and Human Resource Development, 2008)
The implementation of Electronic Data Interchange (EDI) has been the focus of scholars for the past few decades. The tool is viewed as vital for transmission of business data electronically. Despite the substantial benefits, only a fraction of companies worldwide have implemented EDI. Thus, this research is intended to examine the actual scenario of EDI implementation by focusing on manufacturers in Malaysia. The key objectives of this research are to identify EDI barriers, benefits, determinants and present integration levels; to discover the differences existed in EDI barriers, benefits, determinants and integration level based on demographic variables; to examine the influence of barriers, integration level and determinants towards the extent of received or perceived benefits; and to investigate influence of benefits on the improvement in firm performance, based on usersâ€™ perception. This research employs a combination of quantitative and qualitative methods to obtain comprehensive findings. Mail surveys were conducted resulting in 108 usable questionnaires while in-depth interviews were conducted with 6 manufacturers. The findings indicate that there are more â€œmandatedâ€ (type of) users and indirect implementation has become a common practice among the respondents. Organizational aspects are the major determinants; time-based benefits are the key benefits; financial aspects are the critical barriers; and only a few respondents have highly integrated EDI. The findings also indicate that the extent of received or perceived EDI benefits is significantly influenced by the determinants, barriers and level of integration. The level of EDI integration is found to be similar among different types of users; however it differs according to firm size. Only few respondents (44.5%) agreed that EDI benefits have brought positive impacts on their firm. In brief, EDI implementation among these respondents is still at the infancy stage where significant efforts from both authorized parties and users are needed to improve the present scenario.